Pengaruh Literasi Keuangan, Literasi Akuntansi, dan Literasi Digital terhadap Kinerja UMKM Subsektor Usaha Mikro di Kota Pontianak Tahun 2022 - Fadilah, Nadhifah Nur'aini (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of financial literacy, accounting literacy, and digital literacy on the performance of micro-enterprises in Pontianak City in 2022. The study employs a quantitative approach using primary data collected through questionnaires distributed to 100 micro-enterprise owners. The sample was determined using the Slovin formula and selected through non-probability sampling with a convenience sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling with SmartPLS version 4.0. The results show that financial literacy has a positive and significant effect on micro-enterprise performance, accounting literacy has no significant effect, and digital literacy has a positive and significant effect. The model explains 31.9% of the variation in micro-enterprise performance. These findings indicate that financial and digital capabilities are important resources for improving business performance, while accounting literacy does not directly contribute to performance in the context examined.